117 SPLIT HAND-SPLIT FOOT MALFORMATION 3 AT 10Q24: CLINICAL AND LABORATORY DIAGNOSIS AND GENE SEARCH. (1st January 2006) - DeLozier, C. D.; Lyle, R.; Radhakrishna, U.; Schwartz, C.; Antonarakis, S. E.; Blouin, J. L.
Abstract : Split hand/split foot disorder (SHFM, also called ectrodactyly) is a clinically and genetically heterogeneous group of congenital limb malformations, which includes syndromic and nonsyndromic forms. The typical limb defect is a deep median cleft due to absence of the central rays, affecting from one to all four members, with feet more often and more significantly affected than hands. SHFM can, however, present with a range of malformations of highly variable severity even within a family. The inheritance pattern in most families is autosomal dominant, with variable penetrance. However, autosomal recessive and X-linked forms have also been described. Five SHFM loci have been mapped: SHFM1 (7q21), SHFM2 (Xq26), SHFM3 (10q24), SHFM4 (3q27), and SHFM5 (2q31). To date mutations in a specific gene (TP63) have been identified only for SHFM4. We have studied three large families with SHFM3, showing the classical autosomal dominant transmission and variable severity. After first mapping these families to 10q24, we have worked on defining the mechanism of gene disruption, which can be shown by pulsed-field gel electrophoresis to be caused by an approximately 500 kb DNA rearrangement. This region contains a number of candidate genes for SHFM3, but the gene or genes involved in the pathogenesis of SHFM3 are not yet known. We have developed a diagnostic test for SHFM3 that uses two different techniques, FISH and quantitative PCR, to show that SHFM3 is caused by a minimal 325 kb duplication containing only two genes (BTRC and POLL). The data presented provide improved methods for diagnosis and begin to elucidate the pathogenic mechanism of SHFM3, as at least 2 genes of 13 studied from the 10q24 region are overexpressed in SHFM3 patients as compared to controls.